Mechanical Engineering design selected, peer reviewed papers from the first International Conference on Mechanical Engineering Design 2016 (ICMED 2016), April 25-26, 2016, Chennai, India - Salvaraj, M. (Applied mechanics and materials, 2016)
ICMED'16 addresses key topics and issues related to all aspects of Mechanical and Multidisciplinary Engineering Design. Conference program include technical sessions, panel discussions, symposiums, tutorials, demos, and workshops and plenary/keynote speeches. The Conference will be held in Chennai, TamilNadu, India during April 25-26, 2016. Accepted and presented papers will be published to peer-reviewed journals